EFFEKTIFITAS PENGGUNAAN T-JUNCTION DENGAN VARIASI HAMBATAN GUNA MEMISAHKAN KEROSIN DAN AIR DALAM INSTALASI PEMIPAAN - Suhartoyo; Karminto (JMIO, 2021)
This study aims to determine the effectiveness of separating kerosene and water in a piping installation using T-Junction and variations in resistance. It is very important to do research because it can reduce problems that arise in the distribution of drilling oil to the next distribution. T-Junction is a method used in this study, because the separator method is rarely used. Separation of kerosene type oil and water in the test. 42%, 57% and 72% are variations of downstream resistance. At the superficial velocity of the mixture 0.35 m/s, Jw= 0.25 m/s and Jk = 0.10 m/s from the tests carried out, the kerosene separation efficiency was 100%. At a mixed superficial velocity of 0.47 m/s Jw = 0.22 m/s and Jk=0.25 m/s also produces an efficiency of 100%, while at a mixed superficial velocity of 0.20 m/s Jw= 0.10 m /s and Jk = 0.10 m/s produce an efficiency of 99%.